Epithelial-mesenchymal transition of cancer cells using bioengineered hybrid scaffold composed of hydrogel/3D-fibrous framework - Pal, Mintu (2019)
Cancer cells undergoing epithelial-mesenchymal transition (EMT) acquire stem cell-like phenotype associated with malignant behaviour, chemoresistance, and relapse. Current two-dimensional (2D) in-vitro culture models of tumorigenesis are inadequate to replicate the complexity of in-vivo microenvironment. Therefore, the generation of functional three-dimensional (3D) constructs is a fundamental prerequisite to form multi-cellular tumour spheroids for studying basic pathological mechanisms. In this study, we focused on two major points (i) designing and fabrication of 3D hybrid scaffolds comprising electrospun fibers with cancer cells embedded within hydrogels, and (ii) determining the potential roles of 3D hybrid scaffolds associated with EMT in cancer progression and metastasis. Our findings revealed that 3D hybrid scaffold enhances cell proliferation and induces cancer cells to undergo EMT, as demonstrated by significant up-regulation of EMT associated transcriptional factors including Snail1, Zeb1, and Twist2; and mesenchymal markers whereas epithelial marker, E-Cadherin was downregulated. Remarkably, this induction is independent of cancer cell-type as similar results were obtained for breast cancer cells, MDA-MB-231 and gastric cancer cells, MKN74. Moreover, the hybrid scaffolds enrich aggressive cancer cells with stem cell properties. We showed that our 3D scaffolds could trigger EMT of cancer cells which could provide a useful model for studying anticancer therapeutics against metastasis.